Antiproliferative activity of selected prophetic medicinal plants on human lung adenocarcinoma cells, A549 - Abdul Ghani, Radiah; Jamil, Elyna Fatini; Nor Azahan Shah, Nor Azni Masturah; Nik Abdul Malek, Nik Nurasyikin (2015)
Introduction: Cancer incidence has shown marked increase over the years that lead to significant interest in disease prevention strategies. Chemoprevention is one of the potential approaches using natural, synthetic or biological agents that are able to delay, reverse, or prevent cancer initiation. Using natural agents of recommended prophetic medicinal plants is our main focus owing to not much study has elaborated on them. Therefore, the aim of the present study is to investigate the effect of selected prophetic medicinal plants as potential cancer chemopreventive agents using fig (Ficus auriculata), dates (Phoenix dactylifera), and raisin (Vitis vinifera) against A549 cells. Methods: The plants were freeze dried with freeze-drying machine, diluted to a certain concentration and tested for antiproliferative activity using MTT and trypan blue (TB) exclusion assay. IC50, cell number and cell viability (%) were determined. Results: All plants showed significant dose-response relationship against A549. Fig and dates inhibited 50% of the cell population at concentration of 25 mg/ml while raisin at 30 mg/ml respectively. Growth curve indicated cell number was reduced over time from 0 to 144 hour and cell viability was ranged from 98.4-0%. Conclusion: The results suggested that selected prophetic medicinal plants tested displayed growth inhibitory effect in A549 cells.